Analysis of Work Accidents Based on K3 Knowledge and Work Behavior at Muhammadiyah Hospital in Ponorogo - Rindang Diannita; Indasah Indasah; Sandu Siyoto (Journal for Quality in Public Health, 2020)
Occupational health and safety is a component of the hospital that must be considered by the hospital. The purpose of his research was to find out related to the occurrence of work accidents based on knowledge of occupational safety and health and the behavior of workers at the Muhammadiyah Hospital. The sampling technique was done by proportional cluster random sampling with a cross sectional approach. The population of all employees working at the Muhammadiyah Hospital. The independent variable is knowledge of occupational safety and health and worker behavior, the dependent variable is work accident, the data is collected by being analyzed by logistic regression test. The results showed that there was an effect of occupational safety and health knowledge on the incidence of workplace accidents (significant value = 0.002 <0.05), there was an influence of behavior on the incidence of workplace accidents (significant value = 0.004 <0.05. all aspects of occupational safety and health, and it is recommended that workers comply with the operationalstandards of occupational safety and health procedures at the Muhammadiyah Hospital